EVALUASI MEDIA DAN FREKUENSI PENYIRAMAN TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L) - Reki Hendrata; - Sutardi (Universitas Trunojoyo Madura, 2010)
are oftentimes met by problem of availability irrigating water. The aims of this research was to study the know influence of media and frequency of sprinkler irrigation to growth of seed of cocoa plant, the best of media and also frequency of optimum sprinkler it to growth of seed. The research was conducted in month of April until July 2007 in Wonocatur, Banguntapan subdistrict, Bantul Regency.The experiment was arranged in a factorial completete romdomed design with two factor. The first factor were media ( M) consisted to by 4 level, namely M1 : latosol soil , M2 : latosol soil + organic munure (2:1), M3 : sphagnum, and M4 : sphagnum + organic munure (2:1). The factor second of sprinkler frequency irrigation (P), consisted of 3 level, with P1 : 1 day, P2 : 2 day and P3 : 3 day once, so that obtained 12 combination of treatment three repeated. The results showed that the kinds of media have an in with high seed, leaf amount, diamater, and the length root seed. The media sphagnum + organic manure (M4) give influence tend to compared by better could be leaf amount, high, and the diameter. The media organic manure (M2) which were give effect tend to compared by better of length root grow. The sprinkler irigation 3 day once (P3) show better effect to length root grow seed, although was not interakasion.